1986
DOI: 10.1007/bf02555193
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin secretion in streak gonad syndrome (Turner's syndrome)

Abstract: Osteoporosis in one of the most common complications of streak gonad syndrome (SGS), however, its pathogenesis is still unclear. To test whether SGS is associated with calcitonin (CT) deficiency, 11 affected individuals and 8 age-matched healthy women were studied. Calcium, 3.6 mg/kg b.w. as a 10% solution of calcium chloride, was given intravenously for 3 minutes. Serum levels of CT and calcium were measured before and at 5, 30, 60, and 120 minutes after the injection. There was a statistically significant ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is well estab lished that bone formation is a complex pro cess regulated by a series of humoral and local factors [13,14]. We measured serum levels of the parathyroid hormone, calcito nin, vitamin D metabolites, glycocorticoids, thyroid hormones and prolactin in patients with SGS and found an impaired calcitonin secretion [15,16]. The clinical implication of this finding in relation to bone maturation is not clear since calcitonin docs not have a direct or indirect effect on the bone forma tion [17], Although there are some data sug gesting that growth hormone secretion is im paired in a number of cases of SGS [5,18], bone retardation does not seem to be related to growth hormone deficiency.…”
Section: Discussionmentioning
confidence: 97%
“…It is well estab lished that bone formation is a complex pro cess regulated by a series of humoral and local factors [13,14]. We measured serum levels of the parathyroid hormone, calcito nin, vitamin D metabolites, glycocorticoids, thyroid hormones and prolactin in patients with SGS and found an impaired calcitonin secretion [15,16]. The clinical implication of this finding in relation to bone maturation is not clear since calcitonin docs not have a direct or indirect effect on the bone forma tion [17], Although there are some data sug gesting that growth hormone secretion is im paired in a number of cases of SGS [5,18], bone retardation does not seem to be related to growth hormone deficiency.…”
Section: Discussionmentioning
confidence: 97%
“…Zseli et al reported that a decreased basal level of calcitonin was reported in 11 untreated subjects with Turner syndrome [8]. Turner women may need not only estrogen replacement but also other treatments (intake of calcium, other medication etc.)…”
Section: Discussionmentioning
confidence: 99%